Organic Pollution Carrying Capacity of the BatangArau River, Padang, Sumatra Barat Province - Muhammad Ridho; Sampe Harahap; M. Hasbi M. Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT BatangArau River received organic matter from domestic activities conducted around the river. As the load capacity of a river is limited, any load addition may damage the ecosystem in the river. The aims of this study is to determine the capacity of the organic pollution load of the BatangArau River based on the BOD and COD content. This research was conducted in June 2017. There were 5 stations, in the upstream (S1), in the middle of the river (S2 and S3) and in the downstream (S4 and S5). Water samplings were conducted 3 times, once per week. Parameters measured were BOD and COD. The load capacity was calculated using a mass balance method. Results shown that the BOD content was 4.3 mg/L and COD 17.7 mg/L. Based on government standard (PP. 82 of 2001), the river is categorized as polluted and it may not be able to receive any organic matter load addition.Keyword :Mass balance method, pollution load, organic matter, domestic activities